A survey of optimal process design capabilities and practices in the chemical and petrochemical industries. (6th April 2018) - Tsay, Calvin; Pattison, Richard C.; Piana, Michael R.; Baldea, Michael
Highlights: A survey of optimal process design practices and software tools. Focus on design of continuous processes in a wide spectrum of industries. Interactions between technology development, plant construction, and process operations are revealed. Trends and future recommendations for adoption of optimal design tools are provided. Abstract: To examine industrial capabilities and practices in using process design optimization software tools, we conducted a series of over one hundred interviews with practitioners and industry experts in optimal process design, focusing on current techniques, workflows, and challenges. In this article, we analyze the findings of these interviews, providing a perspective into the status of optimal process design in the petrochemical and chemical industries. We first present the findings categorized by company type and personnel function, followed by industry-specific insights.